Enforcement of Election Administrators' Code of Ethics: Evaluating DKPP Institutional Reform After the 2024 Election - Irmanjaya Thaher; Juanda Juanda (Hakamain: Journal of Sharia and Law Studies, 2024)
This study examines the enforcement of the code of ethics for election administrators in Indonesia by evaluating the institutional role of the Honorary Council of Election Organizers (Dewan Kehormatan Penyelenggara Pemilu/DKPP) following the 2024 elections. The research focuses on the effectiveness of the DKPP in maintaining integrity, accountability, and public trust amid increasingly complex electoral challenges. Employing a normative legal research method, the study analyzes constitutional provisions, statutory regulations, DKPP decisions, Constitutional Court judgments, and relevant academic literature concerning electoral governance and institutional accountability. The findings demonstrate that the DKPP has played a significant role in enforcing ethical standards and safeguarding the professionalism of election administrators through adjudication of ethical violations. Nevertheless, several institutional constraints continue to limit its effectiveness, including overlapping authority with other electoral bodies, inconsistent implementation of ethical decisions, limited preventive oversight, and insufficient legal certainty regarding the binding force of its rulings. The experience of the 2024 elections further reveals the need to strengthen institutional coordination among electoral management bodies while enhancing transparency and procedural fairness in ethical adjudication. This study argues that comprehensive institutional reform should include clearer jurisdictional boundaries, stronger enforcement mechanisms, improved due process guarantees, expanded preventive ethics programs, and greater public participation in monitoring electoral integrity. Strengthening the DKPP through these reforms would reinforce democratic accountability, enhance the credibility of election administration, and contribute to a more transparent and trustworthy electoral system. Ultimately, effective ethical enforcement is indispensable for preserving constitutional democracy and ensuring that electoral governance operates in accordance with the principles of integrity, impartiality, and the rule of law.